Assessing the role of perceived values and felt responsibility on pro-environmental behaviours: A comparison across four EU countries. Issue 101 (November 2019) - Punzo, Gennaro; Panarello, Demetrio; Pagliuca, Margherita Maria; Castellano, Rosalia; Aprile, Maria Carmela
Highlights: We analyse the main factors leading to pro-environmental behaviours (PEBs). We compare France, Germany, Italy, and the United Kingdom. We perform Structural Equation Modelling (SEM) on Eurobarometer data (2017). Values (directly and indirectly) and felt responsibility are determinants of PEBs. Policymakers should focus on values, which act on PEBs through felt responsibility. Abstract: The study aims at providing a better understanding of the main factors leading to environmentally-friendly practices by investigating the relationships among perceived values, felt responsibility, and pro-environmental behaviours. The analysis is performed with reference to four developed European countries – France, Germany, Italy, and the United Kingdom. Based on Eurobarometer data (2017) on the attitudes of Europeans towards the environment, a structural equation modelling approach reveals positive and significant relationships among the three constructs, with interesting cross-country differences. In Italy and the United Kingdom, perceived values are directly associated with pro-environmental behaviour, while in Germany and France, where the cultural European identity appears to be more salient, values provide less guidance for behaviour. These findings may assist policymakers in developing a set of well-designed strategies for strengthening citizens' pro-environmental habits through the reinforcement of values and feeling of responsibility.